Sex- and Age-based Comparison of Key Clinical Markers of Immunity After Heart and Kidney Transplantation - Whitney A. Perry, MD, MS; Jennifer K. Chow, MD; Audrey E. Martino, MD; Nicholas E. Heger, PhD; Aleah Holmes, BS; Alexandra Werner, PhD; Marta Rodriguez Garcia, MD, PhD; Amanda R. Vest, MBBS; Ashtar Chami, MD; Pritha Sen, MD; David R. Snydman, MD (Transplantation Direct)
Background. The combined effects of age and sex impact important posttransplant outcomes. Despite key physiologic differences in metabolic and immune function, older women are often indiscriminately grouped with either young women or older men. We examined sex- and age-based differences in clinical markers of immunity in heart and kidney recipients, with specific attention to those of postmenopausal women. Methods. Blood was prospectively collected before transplantation, and at 1 and 6 mo posttransplantation, alongside 12 mo of clinical data. Patients were stratified by age, biological sex, and menopause status. Absolute lymphocyte count (ALC), CD4+ and CD8+ lymphocyte subsets, total IgG, 4 selected cytokines, estradiol and progesterone, and cumulative incidence of infection were quantified within groups. The relationship between menopause category (premenopausal women, postmenopausal women, men) and 6-mo ALC was tested by linear regression, controlling for multiple confounding variables. Results. The cohort included 40 heart, 23 kidney, and 3 heart-kidney recipients categorized as 10 women older than 50 y, 12 women 50 y and younger, 26 men older than 50 y, and 18 men 50 y and younger. At 6 mo posttransplant, mean ALC among older women (0.59 K/µL) fell to a far lower range of lymphopenia than in young women (0.9 K/µL), older men (0.85 K/µL), and younger men (0.82 K/µL). Postmenopausal women had significantly lower ALC compared with premenopausal women (P = 0.03) and men (P = 0.05). Women older than 50 y also had the greatest cumulative incidence of infection by 1 y compared with other groups. Conclusions. These findings support the concern for increased risk of infection in postmenopausal organ transplant recipients.